2010
DOI: 10.3844/ajavsp.2010.13.19
|View full text |Cite
|
Sign up to set email alerts
|

Application of Meal Feeding and Skip-A-Day Feeding With or Without Probiotics for Broiler Chickens Grown at High-Altitude to Prevent Ascites Mortality

Abstract: Problem statement: Ascites is a common rapid-growth-related problem in broiler chickens grown at high altitude where the partial pressure of oxygen is low and is marginally adequate to support the growth performance and ascites-related variables. A mismatch between the growth of oxygen supplying organs and the oxygen demanding organs causes ascites in broiler chickens. In the present study, broilers were subjected to two types of feed restriction with or without probiotics and changes in the growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
(20 reference statements)
2
17
0
2
Order By: Relevance
“…In the present study, there was no significant difference in AFP content as percentage of body weight among the treatments (Table 3). Similarly, Urdaneta-Rincon & Leeson (2002), Saleh et al (2005), Lippens et al (2009) and Saffar & Khajali (2010) reported that feed restriction had no effect on abdominal fat deposition. Although, some previous investigation has shown that feed restriction resulted in obesity and an increase in abdominal fat in broilers (Zhan et al 2007, Wijtten et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, there was no significant difference in AFP content as percentage of body weight among the treatments (Table 3). Similarly, Urdaneta-Rincon & Leeson (2002), Saleh et al (2005), Lippens et al (2009) and Saffar & Khajali (2010) reported that feed restriction had no effect on abdominal fat deposition. Although, some previous investigation has shown that feed restriction resulted in obesity and an increase in abdominal fat in broilers (Zhan et al 2007, Wijtten et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers had reported no significant difference in body weight of broilers when they received intermittent feeding and broilers fed ad libitum (Saffar & Khajali 2010, Svihus et al 2010. However, Petek et al (2005) demonstrated that IFP effectively decreased body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics have shown to relieve the stress caused by feed restriction and enhance the bird's immunocompetence (Mansoub & Kafshnochi, ). On the other hand, probiotics did not ameliorate the feed restriction adverse effects of on broiler performance (Saffar & Khajali, ). Therefore, the present study aimed to investigate the effect of quantitative feed restriction, with or without Protexin supplementation, on growth rate, feed utilization, mortality, and carcass of Japanese quails.…”
Section: Introductionmentioning
confidence: 99%
“…A number of variations of feed restriction including limiting the time of daily access to feed (Khetani et al, 2009;Onbasilar et al, 2009;Mohebodini et al, 2009), removal of feed for up to 8 h a d or skip-a-day feeding, allowing birds to feed only once/h and feeding once every other day (Demir et al, 2004;Khajali et al, 2007;El-Fiky et al, 2008;Benyi et al, 2009Benyi et al, , 2010Boostani et al, 2010;Saffar & Khajali, 2010), have been evaluated but results have been conflicting (Navidshad et al, 2006;Cornejo et al, 2007;Khetani et al, 2009;Ghazanfari et al, 2010). However, Mohebodini et al (2009) on the respective research indicated that although intermittent feeding through free access to feed during four periods of 2 h (06:00-08:00, 12:00-14:00, 18:00-20:00, and 24:00-02:00) from 7-21 d of age had lower on body weight gain than control (436.3 vs 495.3 g), but had no effect on weight gain during realimentation period from 22-42 d of age.…”
Section: Introductionmentioning
confidence: 99%